2022
DOI: 10.1111/hex.13501
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with patient empowerment in Spanish adults with type 2 diabetes: A cross‐sectional analysis

Abstract: Objective The aim of the present study is to identify factors associated with patient empowerment in people living with type 2 diabetes mellitus (T2DM) in the Canary Islands (Spain). Methods Secondary cross‐sectional analysis was carried out of data obtained in the INDICA study: A 24‐month cluster randomized‐controlled trial evaluating the effectiveness of educational interventions supported by new technology decision tools for T2DM patients. Sociodemographic variables, clinical data (years since diagnosis, gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 67 publications
1
5
0
1
Order By: Relevance
“…Surprisingly, our study did not reveal any correlation between DES and ADDQoL scores, indicating that these two questionnaires likely capture different concepts related to T2D, which aligns with findings from a study in Spain [19]. Changes in how empowered a person feels about managing their diabetes might not correlate directly with changes in their reported diabetes-specific HRQoL.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Surprisingly, our study did not reveal any correlation between DES and ADDQoL scores, indicating that these two questionnaires likely capture different concepts related to T2D, which aligns with findings from a study in Spain [19]. Changes in how empowered a person feels about managing their diabetes might not correlate directly with changes in their reported diabetes-specific HRQoL.…”
Section: Discussionsupporting
confidence: 64%
“…In our study, there was no significant correlation between diabetes empowerment and the age of participants. Previous studies have shown an inverse association between age and empowerment [15,17,19,21,26], which could be explained by lower levels of health literacy observed in older persons with T2D. On the contrary, research by Simonsen et al showed that adults with T2D, aged 27-57 years, had a lower level of empowerment, lower emotional well-being, more psychosocial distress, and less diabetes-related social support than older participants [4].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Intervensi berdasarkan kepada perawatan yang berpusat pada pasien akan efektif dalam meningkatkan pemberdayaan pada pasien dengan diabetes melitus (Duarte-Díaz et al, 2022). Selain itu, penggunaan Cognitive Behavior Therapy (CBT) dinilai efektif dalam membantu mengurangi rasa cemas dan depresi pada pasien dengan diabetes distress (Zhang et al, 2021;Abbas et al, 2023).…”
Section: Pembahasanunclassified